Analysis of Factors Associated with Malnutritions Among Children Under Five in East Kalimantan Province: A Secondary Data Study - Muh. Amri Arfandi; Siswanto; Irfansyah Baharuddin Pakki; Risva; Muhamad Zakki Saefurrohim (Universitas Mulawarman, 2025)
This study aims to analyze factors associated with malnutrition among children under five in East Kalimantan Province using secondary data from 2021-2023. The dependent variable is the proportion of malnutrition, including underweight, stunting, and wasting. Independent variables include the proportion of low birth weight (LBW), complete basic immunization (CBI) coverage, adolescent pregnancy (<19 years), sanitation access, and poverty rate. Multiple linear regression analysis found that these five variables simultaneously have a significant effect on malnutrition prevalence (p=0.025) with a coefficient of determination of 39.5%. CBI coverage was identified as the most significant predictor of malnutrition (p=0.02). These findings highlight the importance of immunization, prevention of adolescent pregnancy, improved sanitation, and poverty reduction to address malnutrition. The study provides a policy basis for enhancing nutrition intervention programs in the region.